Escherichia coli O157:H7 and O157:H(−) Strains That Do Not Produce Shiga Toxin: Phenotypic and Genetic Characterization of Isolates Associated with Diarrhea and Hemolytic-Uremic Syndrome - Schmidt, H. (American Society for Microbiology, 1999)
We have isolated one sorbitol-nonfermenting (SNF) Escherichia coli O157:H7 isolate and five sorbitol-fermenting (SF) E. coli O157:H(−) isolates that do not contain Shiga toxin (Stx) genes (stx). Isolates originated from patients with diarrhea (n = 4) and hemolytic-uremic syndrome (HUS) (n = 2). All isolates harbored a chromosomal eae gene encoding gamma-intimin as well as the plasmid genes E-hly and etp. The E. coli O157:H7 isolate was katP and espP positive. Respective sera obtained from the patient with HUS contained antibodies to the O157 lipopolysaccharide antigen. The stx-negative E. coli O157:H7 isolate is genetically related to stx-positive SNF E. coli O157:H7. All stx-negative SF E. coli O157:H(−) isolates belong to the same genetic cluster and are closely related to stx-positive SF E. coli O157:H(−) isolates. Our data indicate that stx-negative E. coli O157:H7/H(−) variants may occur at a low frequency and cannot be recognized by diagnostic methods that target Stx.